PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA, KOMPENSASI DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA PEGAWAI PADA BADAN PERENCANAAN PENELITIAN DAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN MOROWALI - Arsyad, Fakhruddin M. (Katalogis, 2016)
The aims of this research are: 1) to test and analyze the simultaneous influence of human resource development, compensation, and job characteristics on civil servants’ satisfaction in The Agency of Planning, Research, and Regional Development (Bappeda), Morowali Regency; 2) to test and analyze the influence of human resource development on civil servants’ satisfaction; 3) to test and analyze the influence of compensationon civil servants’ satisfaction; 4) to test and analyze the influence of job characteristics on civil servants’ satisfaction. The type of the research is explanatory to show the relationships between one of more independent variables with dependent variable by selecting 40 samples through purposive sampling. Based on the results of multiple linear regressions analysis test, this study finds that: 1) human resource development, compensation, and job characteristics simultaneously influence civil servants’ satisfaction in The Agency of Planning, Research, and Regional Development (Bappeda), Morowali Regency, both positively and significantly; 2) human resource development has positive and significant influence on civil servants’ satisfaction; 3) compensation has positive and significant influence on civil servants’ satisfaction; 4) job characteristics have positive and significant influence on civil servants’ satisfaction.